ERGONOMIC RISK ASSESSMENT OF THE PRESS MACHINE FOR CASAVA CHIPS IN SMES-KARYA LESTARI JAYA : A CASE STUDY - Hakim, Silviana; Hardianto, Andy; Fuhaid, N.; Hermawan, Dadang (Journal of Applied Engineering Science, 2021)
This article investigates the effectiveness of the posture movement of a pressing machine to mold the cassava crackers. This study is undertaken at Karya Lestari Jaya, which is one of SMEs in Tulungagung, East Java Indonesia. This industry has a problem with the new manual pressing machine which is too stiff and heavy to be handled. The operators complain about feeling sore at upper and lower arms. It means that this activity has a poor posture when the operators are working. This research aims to identify the ergonomic risk factors for the pressing machine and to determine the best recommendation suggested by the operators and the owner of SMEs-Karya Lestari Jaya. We undertake a case study by collecting data from the observation. We analyze the observation data by RULA (Rapid Upper Limb Assessment). Then, we interview eight interviewees to attain the attribute requires in improving the machine. Also, we analyze the best recommendation by using AHP (Analytic Hierarchy Process).  This study yields the score of RULA is 6 which means the posture in pressing the dough or the working facilities needs to be improved immediately. The results from AHP shows the best recommendation is adding the pneumatic system to the pressing machine to lighten the lever. Ultimately, this finding can be beneficial for the company by figuring the posture and evaluating improvement for the machine.
Keywords: ergonomics risk assessment; rapid upper limb assessment (RULA); analytic hierarchy process (AHP)